1997
DOI: 10.1002/pen.11758
|View full text |Cite
|
Sign up to set email alerts
|

Processing and cell morphology relationships for microcellular foamed PVC/wood‐fiber composites

Abstract: In this research, the effects of the materials and the processing conditions on the cell morphology of foamed PVC/wood‐fiber composites were studied with a view to establishing their process‐structure relationships. Each step of microcellular PVC/wood‐fiber composites processing is addressed, including the surface treatment of the wood‐fiber, mixing of polymer and wood‐fiber, manufacture of the composites, the saturation of the composites with gas, microcellular foaming of the composites, and characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(204 citation statements)
references
References 21 publications
7
194
2
1
Order By: Relevance
“…Therefore, the cell-growth became difficult which led to the reduced average cell size. Resistance in the cell growth due to increased melt viscosity and stiffness of matrix after adding the wood-flour/cellulose-fibers has also been reported elsewhere [3,[16][17][18][19][20]. Figure 6 illustrates the variations of void fraction (Equation (1)) and expansion ratio (Equation (2)) of the foamed samples.…”
Section: Heat Deflection Temperature (Hdt)mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the cell-growth became difficult which led to the reduced average cell size. Resistance in the cell growth due to increased melt viscosity and stiffness of matrix after adding the wood-flour/cellulose-fibers has also been reported elsewhere [3,[16][17][18][19][20]. Figure 6 illustrates the variations of void fraction (Equation (1)) and expansion ratio (Equation (2)) of the foamed samples.…”
Section: Heat Deflection Temperature (Hdt)mentioning
confidence: 97%
“…On the contrary, the void fraction and expansion ratio decreased in the case of composites on increasing the filler content. This trend may be expected as the volume expansion ratio and the void fraction during the foaming process is controlled by not only the number of the nucleated cells but also the amount of gas dissolved in the matrix [3,[16][17][18][19][20] . Previous studies have established that increasing the filler content results in the decrease of the volume fraction of the matrix in composites [21].…”
Section: Heat Deflection Temperature (Hdt)mentioning
confidence: 99%
“…Surface modification of wood fiber with a coupling agent has strong effects on both the concentration of gas molecules absorbed by the composites and the cell morphology of the foamed composites produced through a batch foaming process [6,22]. Previous studies showed that a microcellular-foamed structure was better developed in the composites with treated wood fibers than in the composites with untreated fibers because the addition of coupling agent into the formulation helped encapsulate the gas in the composites for the cell growth [6,22]. Consequently, silane was used as a coupling agent to enhance the adhesion between the matrix and the filler.…”
Section: Treatment Of Wood Flourmentioning
confidence: 99%
“…Sorption experiments performed on neat PLA used a gravimetric method as described in previous papers [6,22]. The main purpose of sorption experiments involves estimating the amount of gas absorbed in a polymer (or estimated gas solubility), one of the important factors in the gas foaming process [6,22].…”
Section: Sorption and Foaming Experimentsmentioning
confidence: 99%
See 1 more Smart Citation